Decolonizando os acervos das bibliotecas públicas : formação de coleções de literatura afro-brasileira - Tanus, Gabrielle Francinne de S. C. (Palabra Clave.)
Public libraries are social and political spaces intended to serve all members of the community, and are thus anchored in the discourse of inclusion and democracy in the access to information, products and services. However, there is still a long way to go to achieve diversity and multiculturalism in its spaces, starting with collections. Based on literature from Library Science and Information Science, this article discusses the relationship between public libraries and the construction and development of collections, with a focus on Afro-Brazilian literature. The social role of public libraries is considered, as well as the role of their professionals, librarians, who are seen as agents of change, emphasizing the importance of both, with a view to building a just and democratic society. As such, these professionals should be aware of the relevance of forming and developing collections that provide ready access to books and especially to books by authors of Afro-Brazilian literature, aiming at strengthening both the identity of subjects as well as the Afro-centered thinking in the communities. In short, more democratic libraries require practices of decolonization of their collections through actions and policies which repair these collections.